Sosio Legal Studies of Islamic Law - Fatwai Nasikhaha (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
This article explores the socio-legal approach to Islamic law as an interdisciplinary framework that integrates normative textual analysis with empirical social inquiry. Classical Islamic legal studies have traditionally emphasized scriptural sources and juristic interpretations, often neglecting the socio-cultural contexts in which Islamic legal norms evolve and operate. Through socio-legal studies, Islamic law is understood not only as a divine normative system but also as a dynamic social institution shaped by historical experiences, cultural practices, political structures, and everyday interactions. Key analytical concepts—including legal pluralism, living law, law in books versus law in action, the social construction of law, and the dynamics of legal authority—provide insight into the gap between Islamic legal ideals and their real-life application, particularly within pluralistic societies such as Indonesia. Employing interdisciplinary methods from sociology, anthropology, and legal studies, this article demonstrates the epistemological, substantive, and practical contributions of socio-legal approaches to contemporary Islamic legal scholarship. Ultimately, this study argues that the socio-legal perspective enhances the relevance of Islamic law in addressing contemporary social change while remaining grounded in its normative foundations.